Proportionality of the relationship between rights and ethics in the attitude of Transcendent theosophy and Western human rights - mahdi zare; mahmod hekmatnia (حکمت اسرا, 2023)
Although the school of legal positivism took place as a prominent discourse in the world's scientific environment; But theschool of natural law isalways favored bymany thinkers of the world.With the statements made by the thinkers of natural law, we can say the similarities between this attitude and the foundations ofTranscendent theosophy in the field of the relationship between law and ethics. The most important of these similarities is the adherence of each of the above two groups to fixed moral principles in law and the recognition of the close connection between these two sciences. This research aims to answer the question that what is the relationship between the Transcendent theosophy thinkers and the human rights of the West? The hypothesis of this research is based on the fact that natural rights thinkers believe in the existence ofakind of fixed rights in human legal systems,which they considerbeyond contractualagreements, andTranscendent theosophy thinkers, in addition to seeing rights as divine, believe that moral principles are fixedin They believe in the human system and as such as natural rights, reason ismentioned as oneof the sourcesof measuring and receiving these fixed principles But the divine law,which is comprehensive of morals and rights, is considered perfect for the happiness of man.The school of positivism also does notneed tomatch the ruleswith fixed moral standards in order to recognize the correctness of laws, but only the will of the legislator expresses the correctness of a law. This research is based on analytical-descriptive method and based on library sources.